Harnessing heterologous and endogenous CRISPR-Cas machineries for efficient markerless genome editing in Clostridium - Pyne, M. E.; Bruder, M. R.; Moo-Young, M.; Chung, D. A.; Chou, C. P. (Scientific Reports, 2016)
Application of CRISPR-Cas9 systems has revolutionized genome editing across all domains of life. Here we report implementation of the heterologous Type II CRISPR-Cas9 system in Clostridium pasteurianum for markerless genome editing. Since 74% of species harbor CRISPR-Cas loci in Clostridium, we also explored the prospect of co-opting host-encoded CRISPR-Cas machinery for genome editing. Motivation for this work was bolstered from the observation that plasmids expressing heterologous cas9 result in poor transformation of Clostridium. To address this barrier and establish proof-of-concept, we focus on characterization and exploitation of the C. pasteurianum Type I-B CRISPR-Cas system. In silico spacer analysis and in vivo interference assays revealed three protospacer adjacent motif (PAM) sequences required for site-specific nucleolytic attack. Introduction of a synthetic CRISPR array and cpaAIR gene deletion template yielded an editing efficiency of 100%. In contrast, the heterologous Type II CRISPR-Cas9 system generated only 25% of the total yield of edited cells, suggesting that native machinery provides a superior foundation for genome editing by precluding expression of cas9 in trans. To broaden our approach, we also identified putative PAM sequences in three key species of Clostridium. This is the first report of genome editing through harnessing native CRISPR-Cas machinery in Clostridium.